From Words to Images: The Rise and Treatment of Visual Public Opinion in the Post-epidemic Era - Wu Yi (Universitas Muhammdiyah Yogyakarta, 2021)
The rise of short videos in the Post-epidemic era have caused the migration of Internet traffic to visual content. This new form of media based on communication technology and algorithm technology can arouse more emotional resonances of audiences, which promotes the formation of a Visual Public opinion field. The emergence of this public opinion field not only increases the risk of public opinion crises such as rumors and extreme views, but also points out the current direction of public opinion governance, and shows the importance of making good use of visual communication methods. Based on this, mainstream media needs to integrate and lead the visual public opinion field by entering the video media platform, producing high-quality video content, and reconstructing the visual public opinion ecology; the competent authority should do a good job in the visual public opinion field from the three aspects of ideology, technology and content. Supervision and governance work will promote a good long-term growth of visual public opinion field.